CSR in Islamic Financial Institution : A Literature Review - Anisa Ramadhini Trianaputri; Dodik Siswantoro; Miranti Kartika Dewi (Institute for Research and Community Empowerment (LPPM TAZKIA), 2017)
This study aims to provide a literature review of previous research related to Corporate Social Responsibility (CSR) in Islamic Financial Institution (IFI). This study contains review of 53 published articles throughout 2006-2016, both in the Islamic economic and financial journal and general journal. The literature review is presented into 5 sections, (a) review by journal and publication year, (b) by research type, (c) by methodology used, (d) by research topics and (e) by theme and region. Based on the review by publication year, it shows that the concept of CSR is still a fairly new topic. Most of the studies is still dominated by qualitative research with literature review method. The majority topic is still limited to the general review of the existing CSR practices, which are descriptively presented only. The results of this study are expected to provide a research mapping of CSR in Islamic Financial Institution, so it can inspire the subsequent research to explore potential areas related to this topic. This attempt becomes increasingly necessary, with regards to the rapid development of Islamic business and finance practices around the world.